Israel's restoration : a textual-comparative exploration of Ezekiel 36-39 - Crane, Ashley S. (Vetus Testamentum, Supplements, 2008)
Commentators traditionally use a textual-critical methodology in examining Hebrew and Greek manuscripts to establish an 'original' reading, frequently attributing other variants to scribal error. This book proposes a complementary-textual comparative methodology that treats each Hebrew and/or Greek manuscript with equal value, listening to each voice as a possible interpretive trajectory. This methodology is applied to the restoration of Israel in Ezekiel 36-39, initially on a micro level examining each verse for intra-linguistic and trans-linguistic variants, frequently finding exegetical reasons for variants. The macro application compares Papyrus 967 with extant manuscripts, finding the different chapter order and pericope minus (36:23c-38) due to theological reasons. This comparative methodology can be used with any study dealing with different manuscripts and versions.